Study on the Fatty Acid Extraction from Iraqi Date Palm (Phoenix Dactylifera L.) Hilawi Variety, Seed Oil and Introdnction of Fatty Acids into Certain Types of Therapeutic and Food Ration - Hanoon Nwaedh, Nwaedh Mahdi; Abizov, Eugeniy A. (International Journal of Advanced Science and Technology, 2019)
This study was carried out in order to extract oil from date palm (Phoenix dactylifera L.). hilawi variety, using Soxhlet extraction method. The content of the oil extracted from saturated and unsaturated fatty acids was examinedand diagnostic tests were run with GC/MS (Gas Chromatography / Mass Spectrometry).